The Effect of Pseudoephedrine In the Medical Treatment of Male Infertility - Orhan, İrfan; Onur, Rahmi; Semerciöz, Atilla; Yüzgeç, Veysel; Erdinç, Ali (Fırat University, 2004)
Objective: To investigate the activity of a sympathomimetic drug pseudoephedrine in the medical treatment of male infertility. Materials and Method: Fifty- two sub-fertile patients whom were referred to our clinic due to infertility and with out any determined infertility pathologies in fertility assessments were retrospectively investigated. As a sympathomimetic agent 180 mg pseudoephedrine was administered to 34 patients for a period of one month. No other drugs were administered to the remaining 18 patients; these patients were the group waiting for assistive reproduction techniques. Patients were assessed according to pre- and post-therapeutic ejaculate volume, total motile sperm number and pregnancy. Results: A significant increase was determined in the ejaculate volume in the group of patients whom were treated with pseudoephedrine while no significant differences were found among patients included in both of the both groups regarding the pre- and post-therapeutic testis volumes, hormone parameters, total motile sperm number, and ratio of pregnancies (p

Amaç: Erkek infertilitesinin medikal tedavisinde, sempatomimetik bir drog olan pseudoephedrine'nin etkinliğini araştırmak.Gereç ve yöntem: Polikliniğimize infertilite nedeniyle başvuran ve yapılan fertilite değerlendirmelerinde herhangi bir infertilite patolojisi saptanmayan 52 subfertil hasta retrospektif olarak incelendi. Hastaların 34' üne sempatomimetik ajan olarak bir ay süre ile 180 mg. pseudoephedrin uygulandı. Geriye kalan 18 hasta ise herhangi bir tedavi uygulanmadan yardımcı üreme teknikleri için bekletilen hastalar idi. Hastalar tedavi öncesi ve sonrası ejakülat volümü, total motil sperm sayısı, ve gebelik açısından değerlendirildi.Bulgular: Tedavi öncesi ve tedavi sonrası testis volümleri, hormon parametreleri, total motil sperm sayısı ve gebelik oranları arasında herhangi bir farklılık saptanmayan her iki gruptaki hastalardan, pseudoephedrin uygulanan gruptakilerde ejakülat volümünde anlamlı olarak artış olduğu belirlendi (p
Erkek İnfertilitesi Medikal Tedavisinde Pseudoephedrine'in Etkisi